PARTISIPASI ORGANISASI PEMUDA MASJID DALAM MENINGKATKAN KEGIATAN KEAGAMAAN DI MASYARAKAT - Ashri Azhari; Lilis Karwati; Nastiti Novitasari (Program Studi Pendidikan Masyarakat, Universitas Mulawarman, 2021)
The Mosque Youth Association is a mosque youth organization that was established to uncrease religious activities in the community. This study aims to describe the participation pf mosque yout organizations in increasing religious activities. This research was conducted due to the lack of participation of mosque youth organizations. The reseacrh method used in this study was a qualitative descriptive method with data collection thechniques through interviews, observation, and documentation. The data analysis technique used was data reduction, data display, and conclusing drawing. Based on the result of the study, it shows that 1) The forms of participation of the Mosque Youth Association in increasing religious activities are the participation in the form of ideas, participation in the form of energy, and participation in the form of property/costs. 2) The participation rate of mosque youth associations in icreasing religious activities is di vided into three groups, namely high, medium, and low. 3) Religious activities in the community start from oneself, the attractiveness of the Mosque Youth Association, and the supporting and inhibiting factors of the Mosque Youth Association. Conclusion: Mosque Youth Association activities to increase religious activities in the community are carried out through religious activities such as regular weekly and monthly recitations, tahsin training, ‘maghrib mengaji’, so that religious activities can icrease mutual cooperation activities, add religious characteristics, increase rewards and religious knowledge, establish friendship, and add friends and relations.